Analysis of Comparative Language Styles in the Poetry of Nias Songs (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to describe and analyze the comparative figurative language found in Nias song lyrics. A qualitative approach was employed using content analysis on fifteen traditional Nias songs containing personification and simile. The results reveal that comparative figurative language plays a crucial role in enriching meaning and strengthening emotional expression. Personification endows nature, animals, and inanimate objects with human traits, creating a deep emotional connection between humans and their environment. Meanwhile, simile is used to emphasize meaning through vivid and imaginative comparisons, such as likening pain to a wound rubbed with salt or a lover’s departure to a leaf carried by the wind. These stylistic devices not only enhance poetic aesthetics but also reflect the cultural values, spirituality, and worldview of Nias society. Thus, Nias song lyrics function as a medium of aesthetic expression and a means of preserving local cultural identity.